Simulated weightlessness procedure, head-down bed rest has reversible effects on the metabolism of rhesus macaque - Yuting Li; Xu Zhang; Zhen Xu; Xixia Chu; Zhiqiang Hu; Zhengyang Ye; Caiqin Li; Zhenbo Wang; Bin Zeng; Jingyu Pan; Qian Zhao; Chengbin Zhou; et al. (Molecular Brain, 2024)
Abstract It is a consensus in the international manned space field that factors such as microgravity during the space flight can cause anxiety, depression and other important brain function abnormalities in astronauts. However, the neural mechanism at the molecular level is still unclear. Due to the limitations of research conditions, studies of biological changes in the primate brain have been comparatively few. We took advantage of -6° head-down bed rest (HDBR), one of the most implemented space analogues on the ground, to investigate the effects of simulated weightlessness on non-human primate brain metabolites. The Rhesus Macaque monkeys in the experiment were divided into three groups: the control group, the 42-day simulated weightlessness group with HDBR, and the recovery group, which had 28 days of free activity in the home cage after the HDBR. Liquid chromatography-mass spectrometry (LC-MS) was used to perform metabolomics analysis on specific brain areas of the monkeys under three experimental conditions. Our results show that simulated weightlessness can cause neurotransmitter imbalances, the amino acid and energy metabolism disorders, and hormone disturbances. But these metabolomics changes are reversible after recovery. Our study suggests that long-term brain damage in space flight might be reversible at the metabolic level. This lays a technical foundation for ensuring brain health and enhancing the brain function in future space studies.